PERUBAHAN PENAMAAN OBYEK PADA PENDERITA AFASIA WERNICKE (KASUS: MR. D) - Mutiara Indah Nirmala Dewi (ENSAINS JOURNAL, 2020)
Abstract: Aphasic patient generally shows deficiency in language production, such as objects naming aspects. The name of an object that was been known, and the patient has comprehension about it, caused by aphasia, the name of object is loss. This article discuss about object naming of language production of Wernicke aphasia patient Mr. D. The research method used is case study with data collected using method of observation, interview, record and written data. The result shows that several deviations  of words according to object naming  in Indonesian language. The result research shows that word of objects name or numbers of objects around the home (indoors and outdoors) are difficult to be spoken, also in  personal naming are not accuratelay spoken. Keywords:  Wernicke aphasia, objects naming, language defficiencyAbstrak: Penderita afasia memiliki beberapa kekurangan bahasa, salah satu diantaranya adalah kesulitan dalam penamaan suatu obyek ((object naming). Nama suatu obyek, walaupun sebelumnya sudah dikenal dan dihafal di luar kepala, namun dengan akibat dari satu hal bisa  menjadi pengurangan daya ingat khususnya penamaan obyek. Artikel ini membahas kesulitan dalam penamaan suatu obyek (object naming) pada penderita afasia Wernicke pada Mr.D. Metode penelitian yang digunakan adalah studi kasus dan  proses pengumpulan data menggunakan metode libat, cakap, rekam, catat. Hasil pengamatan yang diperoleh menunjukkan bahwa pasien Mr.D mengalami kesulitan menyebutkan beberapa kata yang berhubungan dengan obyek benda di sekitar tempat tinggal, maupun nama-nama orang baik di dalam rumah maupun di luar rumah.Kata kunci: afasia Wernicke, penamaan objek, penyimpangan bahasa